1982
DOI: 10.1177/002221948201500605
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabilities as a Symptom of Depression in Children

Abstract: The presence of depression in school-age children may not be adequately recognized by teachers. Teachers may be misdiagnosing depressed children as having a specific learning problem. The incidence of depression in 282 children admitted to a child and family psychiatric unit for a variety of emotional/behavioral disorders was investigated. While depression was seen as a major factor in the poor learning of the identified depressed children, very few of these children were seen as having specific learning disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
8

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 9 publications
0
17
0
8
Order By: Relevance
“…Several recent research reports have suggested specific links among LD, depression, and suicide (Brumback & Staton, 1980;Colbert, Newman, Ney, & Young, 1982;Hayes & Sloat, 1990;Livingston, 1985;Maag & Behrens, 1989;Maag, Rutherford, & Parks, 1988;Peck, 1985;Pfeffer, 1986;Weiss, Minde, Werry, Douglas, & Nemath, 1971). Given the life-threatening nature of depression for adolescents with LD, a closer examination of these variables is warranted.…”
Section: Depression and Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Several recent research reports have suggested specific links among LD, depression, and suicide (Brumback & Staton, 1980;Colbert, Newman, Ney, & Young, 1982;Hayes & Sloat, 1990;Livingston, 1985;Maag & Behrens, 1989;Maag, Rutherford, & Parks, 1988;Peck, 1985;Pfeffer, 1986;Weiss, Minde, Werry, Douglas, & Nemath, 1971). Given the life-threatening nature of depression for adolescents with LD, a closer examination of these variables is warranted.…”
Section: Depression and Suicidementioning
confidence: 99%
“…It should be quite apparent that the repeated inability of students with learning disabilities to exhibit competence in academic situations could lead to such feelings of powerlessness in school over the years, and one can hypothesize that these feelings become increasingly negative with increasing years of school failure. As the research on anxiety, academic self-concept, and attribution for failure demonstrates, many adolescents with LD are characterized by this negative pattern of thinking, as described by Beck. During the last decade researchers have documented the occurrence of depression among children and ado-JOURNAL OF LEARNING DISABILITIES lescents with LD (Brumback, Staton, & Wilson, 1980;Colbert et al, 1982;Goldstein, Paul, & Sanfilippo-Cohen, 1985;Gregg et al, 1992;Livingston, 1985;Maag & Behrens, 1989;Stevenson & Romney, 1984). In their early study, Goldstein et al (1985) assessed 85 children with learning disabilities in an alternative school program.…”
Section: Depression and Suicidementioning
confidence: 99%
“…For example, DSM-5 diagnostic criteria of major depression disorder state that children might not show sad, but irritable mood [45]. Depressed children might report unspecific somatic complaints [46] or depression might result in attention problems, leading to misdiagnosis of depressed children as having learning disorders [47]. Similarly, adolescents with substance abuse might show symptoms of learning disabilities [48].…”
Section: Introductionmentioning
confidence: 99%
“…The question of which is the primary condition is currently of interest (e.g., Epstein & Cullinan, 1986;Mokros et al, 1989). Researchers who considered depression to be primary found that children who were identified as depressed had academic and cognitive scores that would classify them as learning disabled (Colbert, Newman, Ney, & Young, 1982;Weinberg et al, 1989). On the other hand, a number of researchers have proposed that depression results from the diagnosis of LD (e.g., Maag & Behrens, 1989;Mokros et al, 1989).…”
mentioning
confidence: 99%